Design and optimization of a pitch-teeter coupling and the free teeter angle for a two-bladed wind turbine to reduce operating loads - Torben Carstensen (2015)
A possibility to reduce the cost of energy is the use of two-bladed wind turbines. However, the rotor design causes higher dynamic forces on two-bladed turbines, which can be counteracted using a teetering hinge. Especially the fatigue loads can be reduced significantly. In this thesis the different parameters of teetering hub and end stop are analyzed and optimized for the fatigue loads. The simulations were conducted according to IEC 61400-1.